Herpes simplex virus esophagitis—clinical challenges in the elderly - Custódio, Sara Fernandes (BMJ Case Rep, 2021)
A 77-year-old woman presented with a 2-week history of malaise, prostration, anorexia, abdominal pain, vomiting and diarrhoea. She had been taking systemic corticosteroids for the past year. During hospitalisation, renal insufficiency, ionic changes and liver function abnormalities were detected and corrected. However, the patient developed total dysphagia. UGE revealed multiple shallow ulcers below the cricopharyngeal level and in the distal oesophagus, with normal-appearing intervening mucosa. Histological examination allowed the diagnosis of herpes simplex virus esophagitis. Treatment with intravenous acyclovir was instituted for 14 days. In the elderly, herpetic esophagitis may present with non-specific complains, such as prostration or anorexia. In the reported case, dysphagia was only detected as a late symptom, addressing the importance of maintaining a high degree of suspicion for the diagnosis of herpes simplex virus esophagitis.